Imaging Heat and Mass Transfer Processes Visualization and Analysis - Panigrahi, Pradipta Kumar; Muralidhar, Krishnamurthy; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Imaging Heat and Mass Transfer Processes: Visualization and Analysis applies Schlieren and shadowgraph techniques to complex heat and mass transfer processes. Several applications are considered where thermal and concentration fields play a central role. These include vortex shedding and suppression from stationary and oscillating bluff bodies such as cylinders, convection around crystals growing from solution, and buoyant jets. Many of these processes are unsteady and three dimensional. The interpretation and analysis of images recorded are discussed in the text.
Refractive Index Methods -- Flow Past Heated Bluff Bodies -- Convection in Superposed Fluid Layers -- Transport Phenomena in Crystal Growth -- Imaging Jet Flow Patterns -- Closure.
Keywords: Engineering; Computer simulation; Visualization; Thermodynamics; Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Visualization; Thermodynamics; Simulation and Modeling